Women Empowerment Through Handicrafts of Mask Connectors During Covid 19 Pandemics in Kerinjing Village - Hamidi, Ichsan; Taufiq, Taufiq; Mukhlis, Mukhlis; Sukanto, Sukanto; Atiyatna, Dirta Pratama; Bashir, Abdul; Sari, Dwi Darma Puspita (Sricommerce: Journal of Sriwijaya Community Services, 2022)
This service program aims to provide skills in the form of providing hand care training through making mask connectors and how to market them so that they can increase the income of the people of Kerinjing Village. In addition, the product of this training is also expected to be a superior product in rural areas in Kerinjing Village. The method used in this program is carried out through several stages, including the stage of building commitment, the stage of community organizing, the stage of needs assessment, and the stage of planning activities and implementing activities. The results of this activity include hand washing products through the manufacture of mask connectors that have a selling value so that they can increase the household income of the women's group in Kerinjing Village, Tanjung Raja District. Furthermore, this product is also expected to be one of the superior products of this village. In addition, the results of this activity are in the form of marketing assistance through social media through Facebook and Instagram.